MAURO TEIXEIRA JR, FRANCISCO DAL VECHIO, PEDRO M. SALES NUNES, ANTONIO MOLLO NETO, LUCIANA MOREIRA LOBO, LUIS FERNANDO STORTI, RENATO AUGUSTO JUNQUEIRA GAIGA, PEDRO HENRIQUE FREIRE DIAS, MIGUEL TREFAUT RODRIGUES (2013) A new species of Bachia Gray, 1845 (Squamata: Gymnophthalmidae) from the western Brazilian Amazonia. Zootaxa, 3636(3): 401–420. - Teixeira, Mauro Jr; Vechio, Francisco Dal; Nunes, Pedro M. Sales; Neto, Antonio Mollo; Lobo, Luciana Moreira; Storti, Luis Fernando; Gaiga, Renato Augusto Junqueira; Dias, Pedro Henrique Freire; Rodrigues, Miguel Trefaut (Zootaxa, 2013)
Figure 5 caption to read as:FIGURE 5. Sulcate and asulcate faces of (A) left hemipenis of Bachia scaea sp. nov. (MZUSP 103414). and (B) right hemipenis of B. dorbignyi (MZUSP 97914). Scale bar=1mm.